Potential utility of bacterial protein nanoreactor for sustainable in-situ biocatalysis in wide range of bioprocess conditions - Shinde, Yashodhara D.; Chowdhury, Chiranjit (Enzyme and microbial technology, 2024)
Bacterial microcompartments (MCPs) are proteinaceous organelles that natively encapsulates the enzymes, substrates, and cofactors within a protein shell. They optimize the reaction rates by enriching the substrate in the vicinity of enzymes to increase the yields of the product and mitigate the outward diffusion of the toxic or volatile intermediates. The shell protein subunits of MCP shell are selectively permeable and have specialized pores for the selective inward diffusion of substrates and products release. Given their attributes, MCPs have been recently explored as potential candidates as subcellular nano-bioreactor for the enhanced production of indus-trially important molecules by exercising pathway encapsulation. In the current study, MCPs have been shown to sustain enzyme activity for extended periods, emphasizing their durability against a range of physical challenges such as temperature, pH and organic solvents. The significance of an intact shell in conferring maximum pro-tection is highlighted by analyzing the differences in enzyme activities inside the intact and broken shell. Moreover, a minimal synthetic shell was designed with recruitment of a heterologous enzyme cargo to demonstrate the improved durability of the enzyme. The encapsulated enzyme was shown to be more stable than its free counterpart under the aforementioned conditions. Bacterial MCP-mediated encapsulation can serve as a potential strategy to shield the enzymes used under extreme conditions by maintaining the internal microen-vironment and enhancing their cycle life, thereby opening new means for stabilizing, and reutilizing the enzymes in several bioprocess industries.
Keywords: Bioprocess industries; Encapsulation; Enzyme recycling; Enzyme Stability; Microcompartment; Nanobioreactor